Media, communication, culture : a global approach - Lull, James (Cambridge : Polity Press, 2000)
Ideology, consciousness, hegemony. Social rules and power. Culture and cultural power. The active audience. Meaning in motion. Itineraries of the everyday.
Keywords: Culture; Mass media; Mass media and culture